Incentive Complexity, Bounded Rationality and Effort Provision - Johannes Abeler; David B. Huffman; Collin Raymond (Institute of Labor Economics (IZA), 2023)
Using field and laboratory experiments, we demonstrate that the complexity of incentive schemes and worker bounded rationality can affect effort provision, by shrouding attributes of the incentives. In our setting, complexity leads workers to over-provide effort relative to a fully rational benchmark, and improves efficiency. We identify contract features, and facets of worker cognitive ability, that matter for shrouding. We find that even relatively small degrees of shrouding can cause large shifts in behavior. Our results illustrate important implications of complexity for designing and regulating workplace incentive contracts.
Keywords: D8; D9; J2; J3; 330; complexity; bounded rationality; shrouded attribute; ratchet effect; dynamic incentives; field experiments